VLSI Implementation of a 2.8 Gevent/s Packet-Based AER Interface with Routing and Event Sorting Functionality - Scholze, Stefan; Schiefer, Stefan; Partzsch, Johannes; Hartmann, Stephan; Mayr, Christian G.; Höppner, Sebastian; Eisenreich, Holger; Henker, Stephan; Vogginger, Bernhard; Schüffny, Rene (Frontiers in Neuroscience, 2011)
State-of-the-art large scale neuromorphic systems require sophisticated spike event communication between units of the neural network. We present a high-speed communication infrastructure for a waferscale neuromorphic system, based on application-specific neuromorphic communication ICs in an FPGA-maintained environment. The ICs implement configurable axonal delays, as required for certain types of dynamic processing or for emulating spike based learning among distant cortical areas. Measurements are presented which show the efficacy of these delays in influencing behaviour of neuromorphic benchmarks. The specialized, dedicated AER communication in most current systems requires separate, low-bandwidth configuration channels. In contrast, the configuration of the waferscale neuromorphic system is also handled by the digital packet-based pulse channel, which transmits configuration data at the full bandwidth otherwise used for pulse transmission. The overall so-called pulse communication subgroup (ICs and FPGA) delivers a factor 25-50 more event transmission rate than other current neuromorphic communication infrastructures.